Reform of the United Nations Security Council: Equity and Efficiency - Matthew Gould; Matthew D. Rablen (Center for Economic Studies and ifo Institute (CESifo), 2014)
Twenty years of negotiations over reform of the United Nations Security Council (UNSC) are yet to bear fruit. We use recent advances in the theory of a-priori voting power to present a formal quantitative appraisal of the structural reforms contained within eleven current reform proposals, and the separate effect of expansion of the UNSC membership. Only two reform proposals - the EU acting as a single entity, or a weakening of the veto power for permanent members - robustly dominate the status quo against our measures of equity and efficiency. Several proposals may actually worsen the issues they ostensibly claim to resolve.
Keywords: D72; D71; C71; C63; 330; United Nations; United Nations Security Council; United Nations Security Council reform; equity; efficiency; voting power; square-root rule